DEVELOPMENT OF A NEW GENERATION OF TORNUM REX MINING GRAIN DRYERS AND THEIR DESIGN METHODS - V. Fitsyk (Zernovì Produkti ì Kombìkorma)
The materials of the article analyze the problems and methods of drying grain in modern grain dryers. In recent years, the mixed-flow dryer has been the subject of many studies on drying efficiency, dryer control and productivity improvement. However, there is still a significant need for optimization in terms of energy efficiency and drying uniformity. In order to analyze the specific energy consumption and drying uniformity of the technological process, various thermodynamic conditions of the process were investigated, design solutions were investigated using numerical and experimental methods. Based on the results obtained and the aerodynamic analysis of air flows, the design of a new generation TORNUM REX series grain dryer was developed. Pressure losses, drying agent flow distribution and temperature distribution in the hot air chamber in a continuous grain dryer with mixed flow were investigated using CFD (Computational Fluid Dynamics). The flow in the dryer was considered as steady, laminar and turbulent. It is important that the grain is dried evenly, since uneven drying can lead to spoilage of the final product during storage. The graphic practical materials of the article provide the design of TORNUM REX shaft grain dryers, a general view of the movement of air flows in the REX series grain dryer, diagrams of air flow speeds in the grain shaft, a diagram of the distribution of air flows in the temperature spectrum in the REX series grain dryer, a diagram of the formation of the drying agent during mixing with recuperation air in the REX series grain dryer. It was found that different temperature distributions in the output sections can lead to improper drying or damage to the final product, which influenced the change in the design of the dryer. To reduce pressure loss and increase the uniformity of the flow entering the subchamber of the linear gas burner, a new design of the air mixing section and guide vanes in different designs of hot air chambers is proposed. This approach to modeling using CFD can be applied to new technological processes, as well as to evaluate and optimize already established conventional systems.